Absence of remote earthquake triggering within the Coso and Salton Sea geothermal production fields. Issue 2 (21st January 2017) - Zhang, Qiong; Lin, Guoqing; Zhan, Zhongwen; Chen, Xiaowei; Qin, Yan; Wdowinski, Shimon
Abstract: Geothermal areas are long recognized to be susceptible to remote earthquake triggering, probably due to the high seismicity rates and presence of geothermal fluids. However, anthropogenic injection and extraction activity may alter the stress state and fluid flow within the geothermal fields. Here we examine the remote triggering phenomena in the Coso geothermal field and its surrounding areas to assess possible anthropogenic effects. We find that triggered earthquakes are absent within the geothermal field but occur in the surrounding areas. Similar observation is also found in the Salton Sea geothermal field. We hypothesize that continuous geothermal operation has eliminated any significant differential pore pressure between fractures inside the geothermal field through flushing geothermal precipitations and sediments out of clogged fractures. To test this hypothesis, we analyze the pore‐pressure‐driven earthquake swarms, and they are found to occur outside or on the periphery of the geothermal production field. Therefore, our results suggest that the geothermal operation has changed the subsurface fracture network, and differential pore pressure is the primary controlling factor of remote triggering in geothermal fields. Key Points: Remote triggering in geothermal fields is different from surrounding areas Geothermal production affects subsurface fracture network within geothermal fields Differential pore pressure primarily controls remote triggering in geothermal areas